EFFECTS OF TEMPERATURE ON AUSTENITIZING GRAIN SIZE STEEL 31CrMoV9 - V. A. Lutsenko; T. N. Golubenko; O. V. Lutsenko; S. N. Shehurdin (Литьë и металлургия)
Austenitizing studied the effect of temperature on austenite grain size of the chrome-molybdenum-vanadium steel. It is shown that at austenitizing 850–1050ºS in the structure of chrome-molybdenum-vanadium steel nominal diameter of austenite grain varies from 0,063 to 0,084 mm.